Speaking unplugged, or what to do to get ESL students chatting (from a teaching experience at a technical university) - Ekaterina N. Karakozova; Yuliya S. Perevezentseva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The present paper describes an experiment aimed at the development and promotion of communication skills in students at technical higher educational institutions. This article analyzes the possibilities of such an interactive method as free-speaking activity in English classes with a group of students for whom verbal communication was not of interest due to the inability to listen to the interlocutor, differences in the level of language proficiency, and psychological incompatibility with people involved in communication. The principle of training laid down in the research implied a certain sequence of actions that had specific goals and training objectives. The study is based on the comparative analysis of the results of role-play interviews performed by students – “job seekers” – prior to and after the application of the aforementioned approach. The results obtained, first of all, indicate the possibility of successfully regulating the balance of communicative activity in the classroom, which naturally reduces the time of speaking for the teacher and increases the time for developing and improving speaking skills for students. Second, through the use of this method, students overcame psychological barriers caused by the fear of speaking and making mistakes. In general, the experiment facilitated not only influencing the improvement of students’ speaking skills, but also discovering the high potential of the free-speaking activity method for non-linguistic universities, where, as is known, foreign language learning is not a leading subject.